"'Tis yourself is a skeleton": deathbed scenes and ethnic identity in Irish-American short fiction, 1895–1910. Issue 1 (2nd January 2022) - Cusack, Christopher; Janssen, Lindsay
ABSTRACT: Given the putatively axiomatic connection between Irishness and Catholicism, it is not surprising that the ubiquitous deathbed scene in Irish-American fiction is imbricated with the issue of ethnic identity. In romantic didactic fiction, deathbed scenes are not just religiously coded, but also consolidate diasporic figurations of Irishness. However, this article argues that this tradition is not the only guise in which deathbed scenes feature in Irish-American fiction. As we show, some late nineteenth- and early twentieth-century writers of urban realist fiction criticise or satirise the convention to disrupt the dour moralism and ethnic essentialism of writers such as Mary Anne Sadlier and Hugh Quigley. Exploring the dynamics of diasporic memory in fiction by Clara E. Laughlin, James W. Sullivan, Harvey J. O'Higgins, and Kate M. Cleary, this article demonstrates that the deathbed scene is not just used to structure ethno-religious identities, but also to question and subvert such constructions.